The Eco-System, Barriers and Factors of Sustainable Growth Social Economy in Armenia - Malkhasyan, Anna (Journal of Sociology: Bulletin of Yerevan University, 2020)
Thanks to the international donor community, in recent years, the concept of social entrepreneurship has become a factor in the regulation of socio-economic and local problems in Armenia. The article examines the main trends in the development of the social economy. In particular, the author analyzes the institutional aspects and factors of the development of social entrepreneurship. On the basis of expert assessments, recommendations have been developed for a more effective development of the ecosystem of social entrepreneurship.